Indirect Measurement of Electrical Conductivity and Exchangeable Cations on Soil Water Extracts: Assessing the Precision of the Estimates. Issue 9 (September 2016) - Monteleone, Massimo; Lacolla, Giovanni; Caranfa, Gianraffaele; Cucci, Giovanna
Abstract : Abstract: The electrical conductivity of saturated soil paste extracts with respect to the electrical conductivity of extracts obtained applying different soil-water dilution ratios (from 1:1 to 1:5) was estimated considering 194 soil samples of different texture, salinity, and pH. A smaller data set composed by 50 samples was used to estimate exchangeable sodium percentage (ESP) values from the concentration of soluble cations determined on 1:2 water extracts. Both estimation procedures were carried out applying a linear multivariate model, according to a "stepwise" approach. The dilution ratio 1:2 provided the best estimates, although all the dilution ratios gave reasonable results. The ESP prediction model included the concentration of soluble sodium; the addition of electrical conductivity and pH values of the 1:2 soil-water extracts improved precision.